Effect of 15 Days Zinc Loading upon Zinc, Lactic Acid and Creatine Kinase Levels of Wrestlers - IRI, RUCHAN; GOKDEMIR, KADIR; CICIOGLU, IBRAHIM (Asian Journal of Chemistry, 2010)
In order to investigate the effect of zinc loading upon the performance of the sportsmen, some wrestlers were subjected to a 15 d zinc loading and completion period training and their effects on lactic acid, zinc and creatine kinase levels were monitored at rest and after heavy exercise. The study covered 20 wrestlers in University wrestling team. The average ages of the wresters was 23.1 ± 2.46 years for group I and 20.8 ± 1.16 years for group II. The average weights and height of the groups I and II are 81.4 ± 18.18 kg and 173.50 ± 9.61 cm and 72.6 ± 5.67 kg and 169.47 ± 8.65 cm, respectively. The MaxVO2 values of group I and group II were 2.82 ± 0.20 L/min and 2.70 ± 0.10 L/min, respectively. Group II (the control group) was given fruit juice during the 15 d experimental period while the Group I (the experimental group) was administered 2 mg/kg day Zn with fruit juice in the same period. The blood samples necessary for the determination of plasma zinc, lactic acid, creatine kinase and hemograms levels were taken from the wrestlers prior to the zinc loading at resting (D1, D2) and after being subjected to a cycling exercise(D2, K2). The second stage was taking the blood samples after 15 d of loading zinc again at resting (D3, K3) and after cycling exercise (D4, K4). The arithmetic means and standard deviations of the data obtained were computed and ‘t’ test was applied to the differences between the dependent and independent groups and the data were evaluated at p < 0.05 and < 0.01 significance level. It was determined that the administration of zinc increased the muscle strength of the wrestlers and has a positive effect against exhaustion and onperformance by inhibiting the lactic acid release following a 15 d competition period training. The increased levels of zinc were both due to the administration of zinc and heavy training. However the CK levels of the wrestlers were found to be effected from the training but insensitive to zinc loading.